Development of a Discriminative and Biorelevant Dissolution Test Method for Atorvastatin/Fenofibrate Combination with Appliance of Derivative Spectrophotometry - ANUMOLU, Panukumar Durga (Turk J Pharm Sci, 2019)
OBJECTIVES: Nowadays, the market is flooded with combinations of drugs in various dosage forms, but there is a lack of official methods to quantify them. A single dissolution test method for the analysis of combined dosage form is preferred for simplification of quality control testing. MATERIALS AND METHODS: If the developed dissolution medium mimics the biorelevant and discriminating dissolution procedure for drug products with limited drug aqueous solubility it is a useful tool for qualitative forecasting of the in vivo behavior of formulations. RESULTS: Dissolution profiles were evaluated for atorvastatin and fenofibrate in capsules, using a paddle-type United States Pharmacopeia dissolution apparatus in 900 mL of medium at 50 rpm and 37±0.5°C. The best medium was 900 mL of 0.5% w/v sodium lauryl sulfate. The cumulative % dissolution was more than 85% within 45 min for marketed tablets. The proposed dissolution test conditions have discriminative power, dissimilarity factor (f(1)) values are low (12-16%), and similarity (f(2)) factor values are also low (45-48%). Hence the use of 0.5% w/v sodium lauryl sulfate solution is justified. CONCLUSION: The dissolution method was validated (% relative standard deviation <2). To quantify both drugs simultaneously, a second derivative spectrophotometric method was established (λ(max) 281 nm and 296 nm, respectively, for atorvastatin and fenofibrate) in acetate buffer, pH 2.8 solution.